Family Literacy Parenting Strategies Supporting Children During Preschool to Primary School Transition - Fono, Yasinta Maria; Ngura , Elisabeth Tantiana; Wea, Ludgardis (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
The transition from Early Childhood Education (or PAUD in the Indonesian context) to elementary school is a pivotal stage where children shift from